Distribution of endogenous normal tau in the mouse brain. Issue 5 (5th December 2018) - Kubo, Atsuko; Misonou, Hiroaki; Matsuyama, Makoto; Nomori, Akane; Wada‐Kakuda, Satoko; Takashima, Akihiko; Kawata, Mitsuhiro; Murayama, Shigeo; Ihara, Yasuo; Miyasaka, Tomohiro
Abstract: Tau is a microtubule‐associated protein (MAP) that is localized to the axon. In Alzheimer's disease (AD), the distribution of tau undergoes a remarkable alteration, leading to the formation of tau inclusions in the somatodendritic compartment. While the abnormal aggregated tau has been extensively studied in human patient tissues and animal models of AD, how normal tau localizes to the axon, which would be the foundation to understand how the mis‐localization occurs, has not been well studied due to the poor detectability of normal unaggregated tau in vivo. Therefore, we developed immunohistochemical techniques that can detect normal mouse and human tau in brain tissues with high sensitivity. Using these techniques, we demonstrate the global distribution of tau in the mouse brain and confirmed that normal tau is exclusively localized to the axonal compartment in vivo. Interestingly, tau antibodies strongly labeled nonmyelinated axons such as hippocampal mossy fibers, while white matters generally exhibited low levels of immunoreactivity. Furthermore, mouse tau is highly expressed not only in neurons but also in oligodendrocytes. With super resolution imaging using the stimulated‐depletion microscopy, axonal tau appeared punctate rather than fibrous, indicating that tau decorates microtubules sparsely. Co‐labeling with presynaptic and postsynaptic markers revealed that normal tau is not localized to synapses but sparsely distributes in the axon. Taken together, this study reports novel antibodies to investigate the localization and mis‐localization of tau in vivo and novel findings of normal tau localization in the mouse brain. Abstract : Using newly developed antibodies, the physiological distribution of microtubule‐associated protein tau in the mouse brain was visualized at tissue, cellular, and super‐resolution levels. Tau is abundantly distributed in nonmyelinated axons or cell bodies of oligodendrocytes. Super resolution imaging also showed the distribution of tau on axonal microtubules for the first time.